2015
DOI: 10.1007/s10286-015-0291-0
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle training in patients with diabetic autonomic neuropathy: a randomized clinical trial

Abstract: The IMT group had a greater increase in maximum inspiratory pressure as compared to P-IMT (p < 0.05). The IMT improved inspiratory muscle strength in patients with DAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 12 publications
1
25
0
1
Order By: Relevance
“…From them, one observed the reduction of sympathetic nervous activity (SNA), evinced by the reduction of noradrenaline blood levels after the training period 15 . Two other studies have showed an increased in vagal modulation 13 and reduction in the SNA 13,14 , which were pointed out, respectively, by the increase in spectral density in the high frequency band and by the reduction of low frequency band assessed by the HFV ( Table 2). In one study 12 , no changes in autonomic control assessed by HFV measurements with the performance of IMT were observed ( Table 2).…”
Section: Imt Effects On Autonomic Controlmentioning
confidence: 83%
See 3 more Smart Citations
“…From them, one observed the reduction of sympathetic nervous activity (SNA), evinced by the reduction of noradrenaline blood levels after the training period 15 . Two other studies have showed an increased in vagal modulation 13 and reduction in the SNA 13,14 , which were pointed out, respectively, by the increase in spectral density in the high frequency band and by the reduction of low frequency band assessed by the HFV ( Table 2). In one study 12 , no changes in autonomic control assessed by HFV measurements with the performance of IMT were observed ( Table 2).…”
Section: Imt Effects On Autonomic Controlmentioning
confidence: 83%
“…In three studies, the IMT improved autonomic control [13][14][15] . From them, one observed the reduction of sympathetic nervous activity (SNA), evinced by the reduction of noradrenaline blood levels after the training period 15 .…”
Section: Imt Effects On Autonomic Controlmentioning
confidence: 97%
See 2 more Smart Citations
“…This catabolic effect on muscles is induced by more complications including neuropathy, insulin resistance, and chronic low-grade inflammation and may impact the diaphragm muscle negatively. Indeed, neuropathy may play a role in the reduced PI MAX , as a study [22] in patients with T2DM and autonomic neuropathy found reduced PI MAX in their participants. In the present study, most of the patients also suffered from OSA, and when previous and recent data are taken into account, it is difficult to see whether T2DM plays a significant role in the development of impaired IMS.…”
Section: Discussionmentioning
confidence: 99%